Synthesis of extended fluorinated tripeptides based on the tetrahydropyridazine scaffold - Thierry Milcent; Pascal Retailleau; Benoit Crousse; Sandrine Ongeri (Beilstein Journal of Organic Chemistry)
The synthesis of tripeptides incorporating new fluorinated heterocyclic hydrazino acids, based on the tetrahydropyridazine scaffold is described. Starting from simple fluorinated hydrazones, these non-proteinogenic cyclic β-amino acids were easily prepared by a zinc-catalyzed aza-Barbier reaction followed by an intramolecular Michael addition. Preliminary conformational studies on tripeptides including this scaffold in the central position show an extended conformation in solution (NMR) and in the solid state (X-ray).